2014
DOI: 10.3389/fphys.2014.00096
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pannexin-1 hemichannels and purinergic receptors in the pathogenesis of human diseases

Abstract: In the last decade several groups have determined the key role of hemichannels formed by pannexins or connexins, extracellular ATP and purinergic receptors in physiological and pathological conditions. Our work and the work of others, indicate that the opening of Pannexin-1 hemichannels and activation of purinergic receptors by extracellular ATP is essential for HIV infection, cellular migration, inflammation, atherosclerosis, stroke, and apoptosis. Thus, this review discusses the importance of purinergic rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 155 publications
(200 reference statements)
3
71
0
9
Order By: Relevance
“…An emerging literature demonstrates the importance of extracellular ATP purinergic signaling in viral infections, specifically, those caused by HIV-1 (21,22,(31)(32)(33). While limited data on other enveloped viruses exist, it is reported that internalization of pseudotyped HIV was not reduced by purinergic inhibitors (12).…”
Section: Discussionmentioning
confidence: 99%
“…An emerging literature demonstrates the importance of extracellular ATP purinergic signaling in viral infections, specifically, those caused by HIV-1 (21,22,(31)(32)(33). While limited data on other enveloped viruses exist, it is reported that internalization of pseudotyped HIV was not reduced by purinergic inhibitors (12).…”
Section: Discussionmentioning
confidence: 99%
“…This may also explain why anion channels have previously received much less attention than cation channels. It is worth noting that anion channels have been associated with cystic fibrosis, bleeding phenotypes, and inflammatory conditions [12, 13, 15, 26, 27] and may represent valuable therapeutic targets, as demonstrated by clinical use of CFTR modulators [28]. Further work will be required to investigate the contribution(s) by the cohort of platelet anion channels during platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, pannexin-1 channels have been shown to amplify platelet activation responses to threshold agonist concentrations [14]. These ATP-permeable channels are associated with inflammatory conditions and may contribute to atherosclerosis [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, increased proliferation of fibroblasts plays a crucial role in atherosclerotic lesion progression and eventual rupture. This evidence indicates that Pannexin-1 channels, ATP, and P2 receptors are involved in fibroblast proliferation and plaque destabilization [84].…”
Section: Pannexin-1 Channels and Cardiac Fibrosismentioning
confidence: 99%